2007
DOI: 10.1007/s00404-007-0524-0
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy body mass index and adverse pregnancy outcomes

Abstract: Maternal prepregnancy obesity is significantly associated with increased risk of Caesarean section, preterm delivery, pre-eclampsia and macrosomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 16 publications
2
36
0
8
Order By: Relevance
“…By contrast, maternal diabetes, obesity, multipara, excessive gestational weight gain, and post-term pregnancy were associated with LGA [3,6,9,[11][12][13].…”
Section: Brief Communication (Original)mentioning
confidence: 83%
See 1 more Smart Citation
“…By contrast, maternal diabetes, obesity, multipara, excessive gestational weight gain, and post-term pregnancy were associated with LGA [3,6,9,[11][12][13].…”
Section: Brief Communication (Original)mentioning
confidence: 83%
“…Prepregnancy BMI and gestational weight gain have been shown associated with infant birth weight and other obstetric outcomes [6,12]. Previous reports have demonstrated that underweight pregnant women and those with inadequate gestational weight gain according to IOM guidelines, are at increased risk for SGA [9,10,13,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, published studies focused on the associations of maternal anthropometrics with the risk of preterm delivery seem to be inconsistent. Some studies found no association between maternal obesity and preterm delivery, whereas other studies suggested that the risk of preterm birth is higher among obese women (16,(28)(29)(30). A study among 76,682 adolescent women reported that the risk of preterm delivery was lower among women who gained excessively, independently of prepregnancy BMI (31).…”
Section: Obesitymentioning
confidence: 99%
“…A prevalência da obesidade em nosso meio vem aumentando independentemente da idade, raça ou fatores educacionais 29,32,33 . Isso reflete nos elevados índices de sobrepeso e obesidade maternos encontrados em nosso estudo, compatíveis com os encontrados em estudos internacionais, com índices de obesidade variando entre 5,5 a 38,3%, conforme a população estudada 29,33,34 .…”
Section: Discussionunclassified
“…Isso reflete nos elevados índices de sobrepeso e obesidade maternos encontrados em nosso estudo, compatíveis com os encontrados em estudos internacionais, com índices de obesidade variando entre 5,5 a 38,3%, conforme a população estudada 29,33,34 . Durante o crítico período da gestação, o IMC pré-gestacional aumentado e, principalmente, o excessivo ganho de peso podem resultar em importantes problemas para a mãe e seu recém-nascido.…”
Section: Discussionunclassified